Sentimen Analisis Review Aplikasi Skorlife pada Google Play Store dengan menggunakan metode Naïve Bayes - Saputra, Suwanda Aditya (JATISI, 2024)
One of the financial institutions that holds strategic value in the Indonesian economy is the Banking Institution. The relationship between banks and depositors is a contractual relationship between debtors and creditors, based on the principle of prudence, with the aim that banks using customers' funds will be able to repay the funds deposited by the public to them. The Skorlife BI Checking application is presented as a solution to provide better access to credit data and financial reports for users. With the Skorlife BI Checking application, users can easily monitor and manage their financial status, check credit history, and provide suggestions and criticisms from customers to improve the system and services provided. In this case, the author obtained data from comments on the Google Play Store and used the Naive Bayes algorithm. The accuracy results obtained prove that the highest negative comments have an Accuracy of 100% and AUC of 0.500.